1990
DOI: 10.1039/ft9908602291
|View full text |Cite
|
Sign up to set email alerts
|

Infrared, laser-Raman and X-ray diffraction investigation of MoO3/ZrO2 and the oxidation of (Z)-but-2-ene

Abstract: Molybdenum oxide supported on zirconia has been studied by XRD, FTIR and laser-Raman spectroscopy, together with the oxidation of (Z)-but-2-ene. Mo-Zr catalysts with less than 11 wt % of Mo loadings are mainly composed of amorphous polymolybdates. Mo-Zr catalysts with high MOO, loading exhibit high selectivities to acetaldehyde and acetic acid and both Lewis-and Brsnsted-acidic sites by pyridine adsorption. On the other hand, the catalysts with low MOO, loading exhibit selectivities to furan and buta-1,3-diene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…The shift of the bands at 945 and 973 cm -1 to higher frequencies reflects the dehydration of the sample at 673 K; physisorbed H 2 O weakens ModO bonds and it causes the ν(ModO) in MoO x species to shift to lower frequencies. [45][46][47][48][49] The shift of the 897 cm -1 band to 905 cm -1 for isolated tetrahedral MoO 4 species on Al 2 O 3 was attributed by Jeziorowski et al 42 and Wang et al 44 to interactions with the Al 2 O 3 . Treatment at 723 K caused the 905 cm -1 band to weaken gradually and the 833 cm -1 band to become more intense until it emerged as the most intense band in the 800-900 cm -1 region ( Figure 8B,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift of the bands at 945 and 973 cm -1 to higher frequencies reflects the dehydration of the sample at 673 K; physisorbed H 2 O weakens ModO bonds and it causes the ν(ModO) in MoO x species to shift to lower frequencies. [45][46][47][48][49] The shift of the 897 cm -1 band to 905 cm -1 for isolated tetrahedral MoO 4 species on Al 2 O 3 was attributed by Jeziorowski et al 42 and Wang et al 44 to interactions with the Al 2 O 3 . Treatment at 723 K caused the 905 cm -1 band to weaken gradually and the 833 cm -1 band to become more intense until it emerged as the most intense band in the 800-900 cm -1 region ( Figure 8B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The radial structure function shows a scattering peak with a maximum at 3.37 Å (curve c in Figure 5B) 14,[41][42][43][44][45] These studies have concluded that the structure of supported MoO x species depends strongly on the identity of the oxide support, on the Mo content, and on the treatment temperature, but only weakly on the solution pH and on the type of soluble Mo precursor used. Since hydration of supported MoO x samples by exposure to ambient moisture can alter their Raman spectra, [45][46][47][48][49] all spectra in our study were obtained after in situ treatment at the specified temperatures within the Raman cell.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitate of Zr(OH) 4 was obtained by adding aqueous ammonia slowly into an aqueous solution of zirconium oxichloride (Aldrich) at room temperature with stirring until the pH of aqueous solution reached about 8. [21][22][23] The precipitate was washed thoroughly with distilled water until chloride ion was not detected with AgNO 3 solution, and was dried at room temperature for 12 h. The dried precipitate was powdered (100 mesh) by grinding.…”
Section: Methodsmentioning
confidence: 99%
“…These systems are active for various reactions, such as partial oxidation of hydrocarbons and alcohols, [1][2][3][4][5] hydrogenolysis and hydrodesulfurization of crude oil, 6,7 metathesis of alkenes, 8 hydrogenation of benzene, 9 and cracking of hydrocarbons. 10 The conventional way to prepare the catalysts is to impregnate the high surface area support oxide with an aqueous solution of ammonium heptamolybdate followed by calcining the solid in air.…”
Section: Introductionmentioning
confidence: 99%
“…promoted catalysts which are considered to be green catalysts [12][13][14][15][16]. Molybdenum and tungstate based zirconia catalysts are used for several organic reactions such as acetylation, alkylation, esterification, transesterification, 1,3-dioxalanes, biphenyl urea, etc.…”
mentioning
confidence: 99%